2019
DOI: 10.31674/mjn.2019.v11i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Admision Time, Discharge Time and Patients Discharge Type With Length of Stay in Yellow Zone of Emergency Department

Abstract: Patient density in Emergency Department (ED) is an issue that is still being experienced in various countries. Patients density commonly refers to overcrowding that will cause some problems, one of which is the Length of Stay (LOS) of patient in ED. The prolongation of LOS will cause problems for patients (increased mortality and morbidity) and also the staff. The staff who are exhausted also will potentially perform medical mistake that will adversely affect the patient (Salway et al., 2017). Every year, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…DL (complete blood), GDA (random blood sugar / time), FH (faal hemostasis, namely PTT and APTT), liver function (SGOT and SGPT), rapid COV-19, BUN, creatinine, electrolyte serum, and other tests are performed. This is in line with research conducted by Alemu et al, (2019) and Purwacaraka et al, (2019), which explained that laboratory examinations have a strong effect on the Length of Stay in the emergency room. According to the Ministry of Tourism in 2018, the time for laboratory examinations is 140-180 minutes.…”
Section: Resultssupporting
confidence: 91%
“…DL (complete blood), GDA (random blood sugar / time), FH (faal hemostasis, namely PTT and APTT), liver function (SGOT and SGPT), rapid COV-19, BUN, creatinine, electrolyte serum, and other tests are performed. This is in line with research conducted by Alemu et al, (2019) and Purwacaraka et al, (2019), which explained that laboratory examinations have a strong effect on the Length of Stay in the emergency room. According to the Ministry of Tourism in 2018, the time for laboratory examinations is 140-180 minutes.…”
Section: Resultssupporting
confidence: 91%
“…In the research data, the results showed that laboratory tests did not have a significant relationship with LOS lengthening in the ER. This is different from the research of Getahun et al (2019) and Purwacaraka et al (2019) which explains that laboratory tests have a strong effect on LOS in the ER (Getahun et al, 2019; Purwacaraka et al, 2019). It is known that the duration of laboratory examinations depends on the number of laboratory requests determined by doctors and/or specialists.…”
Section: Tabel 4 Regresi Dumy Test Modelmentioning
confidence: 77%
“…The causes of LOS lengthening in the ER are divided into 3 aspects, namely input, throughput, and output (Bellow & Gillespie, 2014). The throughput aspect is the most influential area for LOS in the ER, starting when the patient enters until leaving the ER (Kusumawati et al, 2019;Purwacaraka et al, 2019). The variables in the throughput area include the duration of laboratory examinations, duration of radiological examinations, duration of specialist doctor consultation, and duration of the patient transfer process.…”
Section: Introductionmentioning
confidence: 99%